"Forgetting by not doing": An institutional memory inquiry of forward planning for land production by reclamation. (March 2019) - Lai, Lawrence W.C.; Chau, K.W; Lorne, Frank T
Highlights: First attempt to apply concept of corporate memory to study strategic planning. Original empirical study on reclamation for a small open economy. Original neo-institutional economic inquiry of reclamation. Abstract: Informed by property rights economics, this paper explores some unique advantages of reclamation, as a form of expansionist dynamic zoning, compared to densification of existing built up urban land and conversion of rural and peri-urban land. One major argument is that modern reclamation package, in light of global circulation of capital, can be one comprehensive project that avoids old mistakes and tries out new ideas without upsetting pre-existing development or interests. It then explains, with the help of statistics collected from a historical study of land reclamation of Hong Kong, that the future urban development in this open economy will be arrested if she gives up reclamation. The loss of corporate memory, using civil service staff movements based on the Staff List, seldom used in Hong Kong studies on town planning, as a proxy, in strategic planning is advanced as a factor behind the current situation.